Development of dynamic capabilities for automotive industry performance under disruptive innovation - Atichat Rotjanakorn; Pornrat Sadangharn; Khahan Na-Nan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Dynamic capabilities are creating dramatic change for the industry around the world. Resource-Based View (RBV) theory and Operational capability theory are the basic capabilities of an organization under a normal changing environment. This creates a competitive advantage and organizational success in a relatively short period of time, in which the dynamic environment is not sufficient to cope with this change. Dynamic capability is a concept for managing change under this dynamic environment. Past research supports a direct positive relationship between dynamic capability and firm performance but it did not focus on the mediator variables. This research emphasizes the influences of competitive advantages and innovation capabilities as mediators of dynamic capabilities and firm performance were investigated. A cross-sectional design study was utilised and questionnaires were submitted to 326 firms to test the proposed relationships. IBM SPSS Statistics Base 26, IBM SPSS AMOS 21, and PROCESS macro 3.6 were used for statistical analysis. Results revealed that competitive advantages and innovation capabilities were partially mediated by dynamic capabilities and firm performance. Findings contribute to the literature on empowering leadership and innovative firm performance by highlighting that competitive advantages and innovation capabilities act as mediators to improve dynamic capabilities and enhance innovative firm performance.
Keywords: 650; dynamic capabilities; competitive advantages; innovation capabilities; firm performance